USING FLASHCARDS TO INCREASE STUDENTS’ VOCABULARY - Widya Astuti; Mawardin M. Said; Erniwati Erniwati (Tadulako University, 2022)
The objective of this research is to find out if using flashcards can increase students’ vocabulary of grade VIII students at SMPN 4 Tanantovea Donggala. The researcher used quasi-experimental design with two classes, experimental class consisted of 24 students and control class consisted of 20 students, experimental class and control class. The selected through total sampling technique. In collecting data, the researcher administered pretest and posttest to both the experimental class and control class. The data were analyzed statistically in order to find out the significant difference of students’ achievement before and after treatments.Using 0.05 level of significance and 42 degree of freedom (df), the researcher found that the value of t-table was 2.019, which was lower than the of t-counted (4.65. It means that the hypothesis is accepted. In other words, using flashcards can increase students’ vocabulary.